Comparative Analysis of Islamic Monetary Economic System With the Conventional Monetary Economic System Reviewed From the Stability of the Indonesian Economy - Atika (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this research is to examine empirically how the influence of monetary economic system of Islam in the economic stability in Indonesia and compare it with the conventional economic system. This research is expected to explain that the sharia banking is said still new if compared with conventional banks that have the influence to economic stability in affairs and more effective in improving the welfare of the Indonesian people and to be able to survive in the face of inflation using the system of result sharing. The material used in this research is the request of Islam money variable is all (Depositor funds Third Party) sharia banks in Indonesia. The variables for the results sharing of the form of return (acquisition business activities) from investment contracts from time to time, is uncertain and does not remain in the sharia banks. How big or small of the gains depends on the business results that really obtained by sharia banks. Conventional Money Demand variable is all demand deposit on conventional banks in Indonesia, Conventional Bank Rate variable (BI rate), Variables Gross domestic product (GDP) is the market value of all final goods and services produced in a country in a specific period of time and inflation variables in Indonesia. Observasi data used is variables data in the time frame of the 11 years namely from 2005 to 2015. The data is obtained from the BPS and Bank Indonesia. To perform data processing, author uses software SPSS. Research results on the first model simultaneously prove that the demand for Sharia money and for the results sharing of the effect of the GDP, partially both also affect the GDP. In the second model simultaneously proves that the demand for Sharia money and for the results sharing of the effect of inflation, partially variable only for the results sharing that affect inflation. In the third model simultaneously proves that the demand for conventional money and the BI rate affect the GDP, partially only demand of conventional money (Giral) that affect GDP. On the fourth model simultaneously proves that the demand for conventional money (Giral) and BI rate influence on inflation, partially both also affect inflation.